2009
DOI: 10.2175/106143008x370539
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Tert‐Butyl Ether (MTBE) Degradation by Ferrous Ion‐Activated Persulfate Oxidation: Feasibility and Kinetics Studies

Abstract: The objective of this study was to evaluate the feasibility of using ferrous ion-activated persulfate oxidation to remediate groundwater contaminated with methyl tert-butyl ether (MTBE). In this study, batch experiments were conducted to evaluate the effects of various factors on the efficiency of MTBE degradation including persulfate concentrations, ferrous ion concentrations, and persulfate coupled with hydrogen peroxide. Results show that ferrous ion-activated persulfate oxidation was capable of degrading M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Therefore, the molar ratio of S 2 O 8 2À /Fe 2+ in a persulfate oxidation system is an important controlling factor for effective diesel removal. Chen et al [44], Rastogi et al [45], and Liang et al [46] obtained similar results for MTBE, PCB, and TCE treatment, respectively. All of these findings suggest that the molar ratio of persulfate and the iron-based activator must be optimized.…”
Section: Effects Of Fes Dosementioning
confidence: 69%
“…Therefore, the molar ratio of S 2 O 8 2À /Fe 2+ in a persulfate oxidation system is an important controlling factor for effective diesel removal. Chen et al [44], Rastogi et al [45], and Liang et al [46] obtained similar results for MTBE, PCB, and TCE treatment, respectively. All of these findings suggest that the molar ratio of persulfate and the iron-based activator must be optimized.…”
Section: Effects Of Fes Dosementioning
confidence: 69%
“…The batch reactors were not disturbed to simulate the nearly static subsurface conditions. A pseudo-first order reaction model was applied to investigate the kinetics of diesel removal based on the results of previous studies [30,34,43]. …”
Section: Batch Kinetic Experimentsmentioning
confidence: 99%
“…Thus, excess addition of ferrous ion may reduce the efficiency of contaminant removal [20,21]. Chen et al [43] reported that MTBE degradation rates were positively related to ferrous ion concentrations within the molar ratios of S 2 O 8 2− /Fe 2+ between 1/0.03 and 1/0.3. However, MTBE oxidation rate decreased significantly with a S 2 O 8 2− /Fe 2+ molar ratio of 1/1 due to the competition for sulfate free radicals between ferrous ion and MTBE.…”
Section: Diesel Oxidation Under Different Ferrous Ion Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many occasions chemical methods were applied as an effective and commercially feasible water treatment technique to remove chemical contaminants through several approaches such as precipitation, oxidation or reduction and other chemical reactions that involved exchange of electrons between atoms [10][11][12][13]. In an advanced oxidation processes (AOPs), chemical, electrical or irradiative energy is supplied to the water matrix to produce highly reactive oxidants, which can attack and destroy the target compound.…”
Section: Introductionmentioning
confidence: 99%